TYMPANOPLASTY TYPE-1: DIFFERENT APPROACHES AND THEIR SURGICAL OUTCOMES - Wahid, Fazal I; Manan, Abdul; Saleem, Muhammad; Zada, Bakht; Rehman, Habib -Ur-; Haq, Naseem Ul; Javaid, Muhammad (Pakistan Armed Forces Medical Journal, 2021)
Objective: To calculate the surgical outcomes of different approaches of tympanoplasty type 1 in terms of air bone gap closure, wound healing, and postoperative pain.Study Design: Prospective cross-sectional study.Place and Duration of Study: Department of ENT, Head and Neck Surgery, Medical Teaching Institute (MTI), Lady Reading Hospital (LRH), Peshawar, Pakistan from Jun 2018 to May 2020.Methodology: Size of sample was 75 patients divided into three groups. Consent was obtained from all the patients included in study. After proper evaluation and relevant investigation pre- and post-operative PTA was performed. Tympanoplasty type-1 was performed by the same surgeon by the three approaches following established otological surgical protocol. Collected data was entered in SPSS-25 for analysis.Results: All 75 patients were divided into three equal groups. Male were 55 (73.3%), females were 20 (26.7%). Male: female ratio was 2.7:1. Majority of patients presented in 2nd and 3rd decades of life 31 (41.33%) and 28 (37.33%) respectively. Preoperative mean ± SD, ABG in groups A, B and C were 37.60 ± 11.28 dB, 37 ± 9.68 dB and 31.80 ± 12.40 dB, respectively. No significant difference was found amongst the three groups regarding pre-operative and post-operative ABG (p=0.85 and p=0.4), respectively. Mean ± SD, wound healing time in Groups A, B and C were 1.00 ± 0.00, 1.80 ± 0.40 and 1.76 ± 0.43 respectively with p=0.0001 and similarly postoperative pain with p=0.001. The wound healing time and post-operative was statistically better (p